Long-term live-cell imaging of GFAP+ astroglia and laminin+ vessels in organotypic mouse brain slices using microcontact printing - Christian Humpel (Frontiers in Cellular Neuroscience)
Organotypic brain slices are three-dimensional, 150-μm-thick sections derived from postnatal day 10 mice that can be cultured for several weeks in vitro. However, these slices pose challenges for live-cell imaging due to their thickness, particularly without access to expensive two-photon microscopy. In this study, we present an innovative method to label and visualize specific brain cell populations in living slices. Using microcontact printing, antibodies are applied directly onto the slices in a controlled 400-μm-diameter pattern. Astrocytes are labeled with glial fibrillary acidic protein (GFAP), and vessels are labeled with laminin. Subsequently, slices are incubated with secondary fluorescent antibodies (green fluorescent Alexa-488 or red fluorescent Alexa-546) and visualized using an inverted fluorescence microscope. This approach offers a cost-effective and detailed visualization technique for astroglia and vessels in living brain slices, enabling investigation to be conducted over several weeks.